2020
DOI: 10.1155/2020/3764193
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Transient Receptor Potential (TRPC) Channels in Nociception and Pathological Pain

Abstract: Chronic pathological pain is one of the most intractable clinical problems faced by clinicians and can be devastating for patients. Despite much progress we have made in understanding chronic pain in the last decades, its underlying mechanisms remain elusive. It is assumed that abnormal increase of calcium levels in the cells is a key determinant in the transition from acute to chronic pain. Exploring molecular players mediating Ca2+ entry into cells and molecular mechanisms underlying activity-dependent chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 128 publications
(197 reference statements)
0
17
0
Order By: Relevance
“…Similar to TRPV1 and TRPA1, canonical transient receptor potential (TRPC1-7) channels also mediate Ca 2+ and Na + cell influx [63]. TRPC channels have been shown to be expressed in sensory neurons and their contribution to nociception and pathological pain is well established [63].…”
Section: Trends Trends In In Pharmacological Pharmacological Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to TRPV1 and TRPA1, canonical transient receptor potential (TRPC1-7) channels also mediate Ca 2+ and Na + cell influx [63]. TRPC channels have been shown to be expressed in sensory neurons and their contribution to nociception and pathological pain is well established [63].…”
Section: Trends Trends In In Pharmacological Pharmacological Sciencesmentioning
confidence: 99%
“…Similar to TRPV1 and TRPA1, canonical transient receptor potential (TRPC1-7) channels also mediate Ca 2+ and Na + cell influx [63]. TRPC channels have been shown to be expressed in sensory neurons and their contribution to nociception and pathological pain is well established [63]. It has been suggested that S1P directly activates TRPC1 and TRPC5 in neurons [9] and an indirect activation pathway through S1PR3-Gαq-PLC has also been proposed [9,64,65] ( Figure 3).…”
Section: Trends Trends In In Pharmacological Pharmacological Sciencesmentioning
confidence: 99%
“…Transient receptor potential cation channel subfamily C members (TRPC1–TRPC7) are non-selective cation channels, which can mediate transmission of different forms of sensory information when activated by G protein-coupled receptors in various tissues ( Sun et al, 2020 ). Among them, transient receptor potential cation channel subfamily C member 4 (TRPC4) and member 5 (TRPC5) are expressed in primary sensory neurons and have been implicated in itch and pain ( Westlund et al, 2014 ; Wei et al, 2015 ; Lee et al, 2020 ; Sun et al, 2020 ; Sadler et al, 2021 ). We have recently characterized the expression of TRPC4 in primary sensory neurons expressing CGRP and demonstrated a functional and therapeutic role of TRPC4 in primary sensory neurons in an animal model of psoriasis ( Lee et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prdm12 seems to be fundamental to support of nociceptor neurons (Vervoort et al 2015;Walters 2018), and acts on mechanical nociception in Hexapoda (Nagy et al 2015;Walters 2018), while Pkd2 is associated with thermal nociception with cold (Ye et al 2008;Turner et al 2016). The TRP family is involved in broad nociception functions, both thermal (Dhaka et al 2007;Kadowaki 2015;Peng et al 2015a,b ;Himmel et al 2020), mechanical (Vennekens et al 2012;Kadowaki 2015;Sun et al 2020) andchemical (Gallio et al 2011;Venkatachalam et al 2014;Kadowaki 2015).…”
Section: Conservation Of Molecular Sequences Related To Nociception and Painmentioning
confidence: 99%